ANALISIS PENGGADAAN COUNTER SERVICE KHUSUS BOOKING UNTUK MENGURANGI WAKTU TUNGGU DAN MENINGKATKAN KEPUASAN PELANGGAN BOOKING DI DEPARATEMEN SERVICE AUTO 2000 DI JAKARTA - Evaf Maulina; Dewi Dyah Widyastuti (JURNAL MITRA MANAJEMEN, 2022)
Many consumers have not used the booking system to its full potential when receiving service, resulting in a buildup of customer lines during peak hours such as 8 a.m. to 8 a.m., leading the service reception system to perform poorly and mixing up booking and non-booking clients. As a result, clients who make reservations grumble or are unsatisfied since they must wait a long time to be handled by a service adviser. To address this, our writing team conducted a study to determine the desired waiting time for clients by determining the likelihood value where no units are waiting in the system, allowing the writing team to enhance by developing a specific booking counter system. A customized counter booking system is a program designed to improve customer satisfaction by allowing customers who have made reservations to be served quickly without having to wait in line with regular customers. Keyword: Booking, non-booking, booking system, counter service, and customer satisfaction are some of the terms used.